Academic misconduct among Portuguese Economics and Business undergraduate students - a comparative analysis with other major students - Freire, Carla Maria Freitas da Costa (2014)
The main purpose of this study is to understand the demographic, personal and situational determining factors leading to academic misconduct among undergraduate students by comparatively analyzing the differences among Economics and Business students and other major students. Two thousand four hundred ninety-two undergraduate students from different Portuguese Public Universities answered a questionnaire regarding their propensity to commit academic fraud, 640 of whom were Economics and Business students. Results concluded that Economics and Business students can be distinguished from others regarding the likelihood of copying from the other Major students. Younger students admit more readily to the possibility of cheating than older students. Results indicate a greater probability of acceptance of dishonest practices outside the area of Economics and Management and a greater probability of condemnation of improper practices by students of Economics and Management. This indicates that students of Economics and Management are aware that their behavior is incorrect and unacceptable; peer-pressure and the learning process itself constitute the main justifications provided by Economics and Business students for their fraudulent actions. Implications for this practice are discussed.